Hubungan Intensitas Kebisingan Suara Mesin Kapal Dengan Tekanan Darah Anak Buah Kapal Di Pelabuhan Beringin Palangka Raya - Henry Wiyono; Takesi Arisandi; Dewi Sartika Sidabutar (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
The intensity of noise produced by ship engines can cause health problems and environmental comfort. Ship crew members are workers on the ship who are continuously exposed to the noise of the ship's engine. The impact of continuous noise exposure can cause physiological health problems in the form of increased blood pressure. This can be caused by noise that exceeds the Threshold Value will stimulate the hormone aldesterone which can result in increased blood pressure. The purpose of this study was to determine the relationship between the intensity of ship engine noise and the blood pressure of ship crew at Beringin Port Palangka Raya. This type of research is observational analytic cross sectional design. The number of respondents was 85 respondents of ship crew at Beringin Port Palangka Raya. The research instrument used measurement techniques using a sound level meter and tension meter. Data analysis using chi square statistical test. The results of the study are the noise intensity of the ship's engine sound obtained partially exceeds the NAB. The results of blood pressure measurements include 38 respondents experiencing hypertension and 47 respondents normal blood pressure. Based on data analysis of chi square statistical test results p-value: 0.577 means H0 is accepted. So the results of the study there is no relationship between the noise intensity of the ship engine sound with the blood pressure of the crew at Beringin Port Palangka Raya. The conclusion of this study is that the sound of ship engines with noise intensity exceeds the NAB and can affect the health and environment of workers. Things that can be done as a way of control are by workers using personal protective equipment and appropriate work shifts.